That's the Sound of the Police: State-Sanctioned Violence and Resistance Among LGBT Young People Previously Incarcerated in Girls' Juvenile Justice Facilities. (August 2016) - Mountz, Sarah E.
Among lesbian/gay/bisexual/transgender and questioning youth, queer women, transgender, and gender nonconforming youth have been particularly marginalized in social science research, social service settings, and the community, where they are especially vulnerable to violence and significantly more likely to become involved in law enforcement. This is particularly the case for queer young women, transgender, and gender nonconforming youth of color and low-income youth. This article is based on life history interviews with young adults, aged 18–25, who have been incarcerated in girls' detention facilities in the juvenile justice system in New York State. Interviews were analyzed using the Listening Guide and revealed themes related to the prevalence of interpersonal and state-sanctioned violence in participants' lives, participants' tremendous capacity for resiliency, and creative modes of healing.